PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Lusiana Maria Samosir; Ayang Pratama; Yeti Meliany Lubis (JURNAL LENTERA BISNIS, 2024)
This study focuses on the impact of company size, profitability, solvency, and reputation of public accounting firms on audit delay in mining companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The population in this study includes all mining companies listed on the Indonesia Stock Exchange in 2019-2021. The research sample was selected using a purposive sampling method with many samples so that a total of 75 were obtained. The analysis technique used in this study was multiple linear regression analysis. The results of the study stated that partially company size and profitability did not have an impact on audit delay in mining companies listed on the Indonesia Stock Exchange in 2019-2021. On the other hand, solvency and KAP size have an impact on audit delay for mining companies listed on the Indonesia Stock Exchange in the 2019-2021 period. In addition, simultaneously Company Size, Profitability, Solvency, and KAP Reputation affect Audit Delay in mining companies listed on the IDX in 2019-2021. The value of Adjusted R Square is 0.313 with an impact of 31.3% for audit delay and the remaining 68.7% is influenced by other variables outside this study.